TRADISI BULIMAU PADA MASYARAKAT MAKGHA WAY LIMA, KABUPATEN PESAWARAN, LAMPUNG - Ayatulloh; Syahriyah , Fida; Sari, Ratna (Penerbit Lafadz Jaya, 2024)
The tradition of Bulimau in the people of Lampung, especially in Marga Way Lima, Pesawaran Regency, is a ritual that has important cultural and spiritual values. Bulimau, which is usually carried out before the month of Ramadan, is a process of self-purification using water mixed with various types of flowers and lemons (oranges). This study aims to explore and analyze how the process of the belimau tradition and the values that exist in the Bulimau tradition in the context of the Lampung community in the Marga Way Lima. This research uses qualitative descriptive to gain a deep understanding of the practice and meaning of the tradition. Data were collected through in-depth interviews and literature studies. The results of the study show that the Bulimau tradition contains significant religious, social, and cultural values. Religious values are reflected in the main intention and purpose of balimau as a means of self-purification before entering the holy month of Ramadan. Social value can be seen from the involvement of all members of the community in the implementation of this tradition, which strengthens social bonds and a sense of togetherness. Meanwhile, cultural values are reflected in the use of traditional materials and hereditary practices that have been preserved from generation to generation. In addition, the belimau tradition also serves as a means of education for the younger generation about the importance of maintaining personal and environmental cleanliness, as well as introducing them to meaningful local wisdom. Thus, the belly tradition is not just a ritual, but also a cultural heritage that needs to be preserved and appreciated by the wider community. This research is expected to contribute to a more comprehensive understanding of the Bulimau tradition and encourage efforts to preserve it in the midst of modernization and globalization.